Targeting nuc Gene for Detection of Staphylococcus aureus from Bovine Milk Samples of Assam, India and Phenotypic Identification of Antibiotic Resistance - A New Insight - Mrigakshi Gogoi; Pankaj Chetia; Raj Kumar Pegu; Jayanti Datta Roy (Journal of Pure and Applied Microbiology)
Staphylococcus aureus is the leading cause of milk-borne disease in animals and humans worldwide, and it is often contaminated by enterotoxigenic and antimicrobial-resistant S. aureus strains. The current research work was intended to identify the prevalence of S. aureus from samples of bovine milk from various dairy farms and local vendors of Kamrup Metro District, Assam, India, by phenotypic and genotypic identification along with antibiotic resistance profiling. The conventional aseptic methods were implemented for S. aureus isolation from milk in Baird Parker Agar, supplemented with egg yolk and potassium tellurite. Further, the isolates confirmation was carried out using the automated VITEK system and amplification of the S. aureus specific nuc gene by PCR. Antibiotic susceptibility profiling for variety of 16 antibiotics was obtained through the conventional disc diffusion method. Eighty-five presumptive isolates with jet-black colonies with a white halo on Baird Parker Agar were selected. Thirty-eight isolates were eventually confirmed as S. aureus by the automated method and the detection of nuc gene. Antibiotic profiling revealed about 60.52% of the isolates to be multidrug resistant and 55.26a ± 0.01 mm resistant against Kanamycin. The statistical analysis data expressed correlation between Penicillin G and Ampicillin with 42.10b ± 0.01 mm and correlation among Tetracycline, Methicillin and Streptomycin with 10.52h ± 0.01 mm, respectively. Resistance against Kanamycin, Trimethoprim, Cloxacillin, and Nalidixic acid is concerning as such a resistant pattern has not been extensively reported in bovine milk samples in India, which could indicate the possible emergence of MDR S. aureus strains in the study area.